2019
DOI: 10.20485/jsaeijae.10.1_73
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Automation Instructions and Vehicle Control Algorithms on Eye Behavior in Highly Automated Vehicles

Abstract: Increasingly vehicle automation may convey greater capability than it actually possesses. The emergence of highly capable vehicle automation (e.g., SAE Level 4) and the promise of driverless vehicles in the near future can lead drivers to inappropriately cede responsibility for driving to the vehicle with less capable automation (e.g., SAE Level 2). This inappropriate reliance on automation can compromise safety, and so we investigated how algorithms and instructions might mitigate overreliance. Seventy-two dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…Encouragingly, the visual AR and hands-on-wheel reminders worked, that is, they produced high levels of visual attention and hands on wheel prior to the conflict and during all driving. It is also likely that the AR effect can be enhanced further by affecting vehicle control algorithms, which has been shown to improve eyes on road in highly automated vehicles ( Price, Lee, Dinparastdjadid, Toyoda, & Domeyer, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Encouragingly, the visual AR and hands-on-wheel reminders worked, that is, they produced high levels of visual attention and hands on wheel prior to the conflict and during all driving. It is also likely that the AR effect can be enhanced further by affecting vehicle control algorithms, which has been shown to improve eyes on road in highly automated vehicles ( Price, Lee, Dinparastdjadid, Toyoda, & Domeyer, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Going forward, two main solution alternatives present themselves: either the automation is designed so it does not rely on the driver (as in unsupervised automation), or it is designed so that the driver unmistakably understands that it is only a driving assistance system (a teammate) that needs an active driver who shares control at all times (at least when using highly reliable, near-perfection automation as tested here). Perhaps further research using the shared-control paradigm ( Mulder, Abbink, & Carlson, 2015 ) or adaptive automation ( Parasuraman et al, 2000 ), for example, in the form of adaptive vehicle control or warning/intervention algorithms that respond to driver engagement analysis (e.g., Price, et al, 2017 ), are viable ways forward. Note that if drivers do understand the limitations of the automation, or if drivers do not overtrust the automation, then conflicts can easily be handled, as indicated by the majority (72%) of drivers who easily avoided the conflicts.…”
Section: Summary and Concluding Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Automated vehicle feedback plays a critical role in aligning driver expectations with the capability of the automation. Our previous research demonstrated that vehicle behavior is an important component in influencing trust and attention in an automated vehicle (Price et al, 2016;Price et al, 2017). The present study used a relatively underused statistical approach in the human factors community with an attempt to expand the scope of the previous trust model.…”
Section: Discussionmentioning
confidence: 99%
“…The data used in the analysis is a combination of Study 1 outcomes and two follow-up simulator studies (Study 2 and Study 3), each designed to examine a different implementation of a steering algorithm. Study 2 and Study 3 were nearly identical and used the same scenario with some modifications to the objectives (Price et al, 2017). Study 2 explored whether changing steering behaviors (from lane centering to lane keeping) would influence expectations about whether the automation was capable of driving without sustained visual attention and monitoring of the roadway.…”
Section: Expansion Of the Trust Modelmentioning
confidence: 99%